Sigh generation in preBötzinger complex - Yan Cui; Evgeny Bondarenko; Carolina Thörn Perez; Delia N Chiu; Jack L Feldman (eLife)
We explored neural mechanisms underlying sighing in mice. Photostimulation of parafacial (pF) neuromedin B (NMB) or gastrin-releasing peptide (GRP), or preBötzinger Complex (preBötC) NMBR or GRPR neurons elicited ectopic sighs with latency inversely related to time from preceding endogenous sigh. Of particular note, ectopic sighs could be produced without involvement of these peptides or their receptors in preBötC. Moreover, chemogenetic or optogenetic activation of preBötC SST neurons induced sighing, even in the presence of NMBR and/or GRPR antagonists. We propose that an increase in the excitability of preBötC NMBR or GRPR neurons not requiring activation of their peptide receptors activates partially overlapping pathways to generate sighs, and that preBötC SST neurons are a downstream element in the sigh generation circuit that converts normal breaths into sighs.